Changes in natural torsional frequency of horizontally-curved bridge by reinforcement - N. Kunla; B. Puangkird (My University, 2015)
Horizontally curved steel I-girder bridge (HCSIB) has low torsional resistance hence has a high risk of breakage when it vibrates.This study investigated the changes in the natural torsional frequency of an HCSIB when it is reinforced with different types of bracing members.Three-dimensional finite element numerical analysis with Evolution FEA opensource software was applied to an established model of HCSIB.The simulation results showed that the changes in the bridge's natural torsional frequency caused by reinforcement with K, Z, and X-type cross frames were significant and almost equal to each other, and reinforcement with extra X-type cross frames caused a bigger change, but reinforcement with bottom bracings caused a much smaller change.Overall, K-type cross frames are the best choice for reinforcement because they are the most economical while providing virtually the same high torsional frequency as those provided by the other two cross frames.
Keywords: Bridge (graph theory); Natural frequency; Structural Load-Bearing Analysis